Self-efficacy mediates the relationship between perfectionism and life satisfaction in South Korean adults - Kim, Bo Sun; Kim, Minjeong (Social Behavior and Personality, 2022)
Our aim in this study was to provide a better understanding of the links among self-oriented and self-critical perfectionism and life satisfaction by examining the mediating effect of self-efficacy in this relationship. We collected survey results from 300 adults in South Korea and conducted structural equation modeling. The results show that participants' self-efficacy mediated the path from self-oriented perfectionism and self-critical perfectionism to life satisfaction. Further, self-critical perfectionism led directly to life satisfaction. Theoretical and practical implications are discussed.
Keywords: life satisfaction; Perfectionism; self-critical perfectionism; self-efficacy; self-oriented perfectionism